(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
It is possible to improve the development of students’ spatial thinking with various information technologies. We can improve students understanding with three dimensional models, created in the CAD program and special processing it in PowerPoint in the program, together with drafting in three planes. Gradually solving tasks in planes and explaining it in three dimensional models, the solution of concrete task is much clearer, because it is possible to look a situation together in planes and 3D models. The students of three faculties were polled that cognize the students’ opinions about teachers teaching methods in descriptive geometry lessons and analyze spatial understanding of students. A possibility to use information technologies to improve a descriptive geometry lectures have been researched in this work. The most important information about working out methodological materials has been generalized in discussion part. The results of research show that lectures with information technologies using improve students’ understanding of solved tasks during the lectures.